DESCARTES’ CONSIDERATIONS ABOUT THE HUMAN BEING - Eugenijus Vasilevskis (Problemos)
This article is an analysis of Rene Descartes’ considerations about the human being. Those considerations take us into the realm of philosophical anthropology. Referring to its base, Descartes analyzed onthological and ethical problems. Contents of the Human mind and consciousness attracted the great scientist’s attention. His conclusion, "Cogito ergo sum" – If I think, I exist – was dualistic and one-sided. Rational understanding of the human being brought the classics into the wrong propositions of the subject question.